2013
DOI: 10.1007/s10935-013-0292-5
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Partnerships for Chronic Disease Prevention Among Latinos: The San Diego Prevention Research Center

Abstract: Over 20 years ago, university-community partnerships (i.e., Prevention Research Centers [PRCs]) across the United States were funded by the Centers for Disease Control and Prevention to conduct research and training in order to promote health and prevent disease in underserved populations. In 2004, the San Diego PRC (SDPRC) became the first PRC to focus on obesity prevention and HHS Public Access Author Manuscript Author ManuscriptAuthor ManuscriptAuthor Manuscript control in a community of mostly Mexican Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…A few strategies leading to successful collaborations include open, frequent, on-going communication (Elder et al, 2013;Johnson, Zorn, Yung Tam, Lamontagne, & Johnson, 2003), partner-ready leadership (Austin et al, 1999;Johnson et al, 2003;Minkler, Vasquez, Tajik, & Peterson, 2008), and a clear research purpose or agenda (Davey & Ivery, 2009). During a collaborative partnership with the local community, the San Diego Prevention Research Center found that open communication lines lead to quality input and feedback from all partners (Elder et al, 2013). Citing a shared purpose or vision as a necessity, Minkler and colleagues (2008) found a sense of solidarity and shared values led to an enhanced commitment among the partners studied.…”
Section: Strategies To Create Successful Collaborations and Partnershipsmentioning
confidence: 99%
See 4 more Smart Citations
“…A few strategies leading to successful collaborations include open, frequent, on-going communication (Elder et al, 2013;Johnson, Zorn, Yung Tam, Lamontagne, & Johnson, 2003), partner-ready leadership (Austin et al, 1999;Johnson et al, 2003;Minkler, Vasquez, Tajik, & Peterson, 2008), and a clear research purpose or agenda (Davey & Ivery, 2009). During a collaborative partnership with the local community, the San Diego Prevention Research Center found that open communication lines lead to quality input and feedback from all partners (Elder et al, 2013). Citing a shared purpose or vision as a necessity, Minkler and colleagues (2008) found a sense of solidarity and shared values led to an enhanced commitment among the partners studied.…”
Section: Strategies To Create Successful Collaborations and Partnershipsmentioning
confidence: 99%
“…In forming partnerships and collaborations, memorandums of understanding (MOUs) help maintain and solidify long-term relationships among partners (Elder et al, 2013). MOUs include critical components that allow partnerships to grow and flourish.…”
Section: Strategies To Sustain Collaborations and Partnershipsmentioning
confidence: 99%
See 3 more Smart Citations